Cosmic Evolution of Holographic Dark Energy in f(G,T) Gravity - M. Sharif; Ayesha Ikram (Advances in High Energy Physics)
The aim of this paper is to analyze the cosmological evolution of holographic dark energy in f(G,T) gravity (G and T represent the Gauss-Bonnet invariant and trace of the energy-momentum tensor, respectively). We reconstruct f(G,T) model through correspondence scheme using power-law form of the scale factor. The qualitative analysis of the derived model is investigated with the help of evolutionary trajectories of equation of state and deceleration as well as state-finder diagnostic parameters and ωGT-ωGT′ cosmological phase plane. It is found that the equation of state parameter represents phantom epoch of the Universe whereas the deceleration parameter illustrates the accelerated phase. The state-finder plane corresponds to Chaplygin gas model while the freezing region is attained in ωGT-ωGT′ plane.